2018
DOI: 10.1136/gutjnl-2018-316344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anticoagulants and NSAIDs on accuracy of faecal immunochemical tests (FITs) in colorectal cancer screening: a systematic review and meta-analysis

Abstract: FIT accuracy is not affected by OACs and aspirin/NSAIDs use. Based on the current literature, withdrawal of OACs or NSAIDs before FIT screening is not recommended. Future studies should focus on duration of use, dosage and classes of drugs in association with accuracy of FIT to conduct more specific guideline recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…A recent meta-analysis of six original papers involving FIT-positive patients reported that aspirin and OACs do not affect the PPV of FITs for detecting ACRN [10]. However, a meta-analysis for CRC was not performed in this study because most previous studies on this topic only presented results for ACRN and not for CRC.…”
Section: Discussionmentioning
confidence: 89%
“…A recent meta-analysis of six original papers involving FIT-positive patients reported that aspirin and OACs do not affect the PPV of FITs for detecting ACRN [10]. However, a meta-analysis for CRC was not performed in this study because most previous studies on this topic only presented results for ACRN and not for CRC.…”
Section: Discussionmentioning
confidence: 89%
“…These antibodies are specific to human globin so, unlike the traditional gFOBT, they are not prone to interference from any haemoglobin derived from the diet or from any substance that interferes in the redox reaction of guaiac, such as peroxidases. Moreover, a recent systematic review has shown that cessation of oral anticoagulants, aspirin and other non-steroidal anti-inflammatory drugs is not required 22. There are a large number of FIT on the market; many of these are qualitative tests with very little evidence to support their use in any clinical setting.…”
Section: Analytical Considerationsmentioning
confidence: 99%
“…Existing studies on aspirin use report mixed findings that merit further investigation [ 26 30 ]. The USPTF guidelines suggest routine prescribing of aspirin in patients presenting with advanced colorectal polyps unless contraindicated [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other evidence suggests that aspirin may impact on FIT performance. Studies have reported either a potential higher risk of false positive FIT results, no changes in FIT diagnostic accuracy in patients presenting with gastrointestinal symptoms or an increase in FIT sensitivity by aspirin use [ 27 30 ]. There is also uncertainty about the optimum dose for low-dose aspirin use in the prevention of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%